2006
DOI: 10.1103/physreva.73.022705
|View full text |Cite
|
Sign up to set email alerts
|

Positron binding to alkali-metal hydrides: The role of molecular vibrations

Abstract: The bound vibrational levels for J = 0 have been computed for the series of alkali-metal hydride molecules from LiH to RbH, including NaH and KH. For all four molecules the corresponding potential-energy curves have been obtained for each isolated species and for its positron-bound complex ͑e + XH͒. It is found that the calculated positron affinity values strongly depend on the molecular vibrational state for which they are obtained and invariably increase as the molecular vibrational energy content increases.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
45
1
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 15 publications
6
45
1
3
Order By: Relevance
“…In all positronic species except for CN À ,e þ (and to some extent OH À ,e þ ) the position is exclusively contained in a single quantum atom, the one that is more electronegative. This pattern is in line with the results of previous studies, which have considered the 2D positronic distribution maps for various species [40,41,44,49,[52][53][54]58]. The only serious deviation is observed in the case of CN À ,e þ in which both quantum atoms contain comparable populations ($0.3 in carbon versus $0.7 in nitrogen basins).…”
Section: The Positronic Distribution and Its Implicationsupporting
confidence: 92%
“…In all positronic species except for CN À ,e þ (and to some extent OH À ,e þ ) the position is exclusively contained in a single quantum atom, the one that is more electronegative. This pattern is in line with the results of previous studies, which have considered the 2D positronic distribution maps for various species [40,41,44,49,[52][53][54]58]. The only serious deviation is observed in the case of CN À ,e þ in which both quantum atoms contain comparable populations ($0.3 in carbon versus $0.7 in nitrogen basins).…”
Section: The Positronic Distribution and Its Implicationsupporting
confidence: 92%
“…since such conditions are known to promote positron attachment [1,19]. The significance of this point has not received much attention in existing works that investigate positron binding to molecules [9][10][11][12][13][14]. Such a strategy could be usefully applied to other molecules to guide a search aimed at identifying electronically excited states capable of attaching a positron into a Feshbach resonance.…”
Section: Discussionmentioning
confidence: 99%
“…The only molecule for which precise estimates of the positron binding energy are known is the e + LiH system [5][6][7][8]. There have been calculations of positron binding to a number of other molecules [9][10][11][12][13][14] but the accuracy obtained for these systems is relatively low.…”
Section: Introductionmentioning
confidence: 99%
“…Applications have been carried out for the series of alkali hydrides [3][4][5] as well as a number of alkali oxides [6,7]. This work has shown that accurate potential curves can be obtained at the conventional (molecular) CI level, but also that the amount of the correlation energy itself is underestimated by a significant margin at this level of treatment.…”
Section: Introductionmentioning
confidence: 98%
“…This is the main reason why high-l basis functions are required to obtain high accuracy in such calculations [8], since without them it is impossible to obtain a quantitative description of the positron's charge distribution in the neighborhood of each atomic nucleus and its inner shells. However, there is strong evidence to indicate that the missing correlation effects are predominantly atomic in [3][4][5][6][7]. The primary success of the MRD-CI calculations is that, when calculating potential energy curves for positron-molecule complexes without such high-l basis functions, atomic-like correlation effects are underestimated by nearly the same amount over the entire range of bond distance considered.…”
Section: Introductionmentioning
confidence: 99%